PERAN CITRA MEREK MEMEDIASI PENGARUH E-WOM TERHADAP NIAT BELI (Studi Kasus pada Maskapai Penerbangan AirAsia di Kota Denpasar) - Putri, Ni Putu Ayu Kartika Kurnia; Sukawati, Tjokorda Gde Raka (E-Jurnal Manajemen; Vol 8 No 7 (2019)DO - 10.24843/EJMUNUD.2019.v08.i07.p10, 2019)
The purpose of this study was to explain the effect of e-WOM on brand image, e-WOM on purchase intention, brand image on purchase intention, and the role of brand image in mediating the influence of e-WOM on purchase intention. This research was conducted on consumers who intend to use the services of AirAsia airlines domiciled in the city of Denpasar. The number of samples of this study were 110 respondents using purposive sampling. The data were collected by distributing questionnaires using a Likert scale to measure 11 indicators. The analysis techniques used in this study are path analysis (path analysis), sobel test, and VAF test. The results of this study indicate that the e-WOM variable has a positive and significant effect on brand image. This study also found that each e-WOM variable and brand image had a significant positive effect on purchase intention. In addition, the brand image variable is also able to mediate the influence of e-WOM on purchase intentions partially. Keywords: brand image, e-WOM, and purchase intention. Keywords : brand image, e-WOM, and purchase intention